Widening Participation and Accountability in UK Higher Education - Smith , Emma; Mihut, Georgiana (International Higher Education, 2025)
Widening participation remains a key bipartisan aim for higher education policy and practice in the United Kingdom. Universities are held accountable for their widening participation outcomes. Despite these policies, higher education inequalities persist.